Curiosity as a Moderator of the Relationship Between Entrepreneurial Orientation and Perceived Probability of Starting a Business - Barrientos Oradini, Nicolás Pablo; Rubio, Andrés; Araya-Castillo, Luis; Boada-Cuerva, Maria; Vallejo-Velez, Mauricio (Frontiers in Psychology, 2022)
Although the correlation between Entrepreneurial Orientation (EO) and concrete actions to set up a business or the Probability of Starting a Business (PSB) has been widely studied, the psychological factors that can affect this relationship have not yet been sufficiently addressed in the field of entrepreneurship. One of them is curiosity. Both at theoretical and empirical level, a distinction is usually made between two types of curiosity. I-type curiosity is associated with the anticipated pleasure of discovering something new, and D-type curiosity is associated with reducing uncertainty and eliminating unwanted states of ignorance. Consequently, this paper aims to analyse the moderating role that the types of curiosity play in the relationship between EO and PSB, considering their interaction with sociodemographic variables. The sample of this cross-sectional study consisted of 1,761 participants (convenience sampling of active workers), (49.8% men; mean age 38.88 years, SD = 12.53 years; 22.9% Colombian and 77.1% Spanish). The EO scale and a curiosity scale were applied. In addition, participants were asked, based on their perception, how likely they were to start their own business within the next five years. A simple moderation analysis was considered to test the moderating role of both types of curiosity in the relationship between EO and PSB. Next, a double moderation analysis was carried out in order to identify which sociodemographic variables moderate the moderating effect of curiosity. The results show that only the D-type component moderates the relationship between EO and PSB: The higher the D-type curiosity, the stronger the association between EO and PSB. In terms of sociodemographic variables, neither culture nor gender showed a moderating effect on the moderation exerted by D-type curiosity. While, age did moderate the moderating effect of D-type curiosity on the relationship between EO and PSB. Results are discussed in terms of spirituality (attitudes, practices, and behaviors) and the resolution of problems associated with the entrepreneurial process, considering cognitive and psychological factors, particularly with an emphasis on explaining why only D-type curiosity shows a moderating effect. Finally, the limitations of the study and potential future lines of research are pointed out.